(untitled) (Economic studies journal, 2023)
This study examines the role of Cloud Computing Technology(CCT) in enhancing accounting education by identifying the extent to which CCT contributes to the improvement of accounting students ’professional skills, in order to identify the extent to which CCT contributes to improving the teaching of accounting courses. The study also aims to identify the potential challenges of using CCT in accounting education, from the point of view of the lecturers in the Departments of Accounting at University of Derna and Omar Al-Mukhtar University, 50 lecturers have been surveyed to achieve the objectives of the study.A questionnaire used as a main instrument for collecting the study’s data, then analyzed the obtained data using descriptive statistics methods represented in: (Mean, Standard Deviation, Relative Weight). The findings shows that Cloud Computing Technology (CCT) contributes to the development of professional skills for accounting students. In addition, there are many advantages of using CCT in teaching accounting courses. However several obstacles and challenges of using CCT in accounting education. The study concluded with recommendations of which are: to work on the usage of Cloud computing Technology (CCT) in improving and developing accounting education, and work on developing and continuously updating the accounting study plan in line with Cloud Computing Technologies.